A TADF Emitter Featuring Linearly Arranged Spiro‐Donor and Spiro‐Acceptor Groups: Efficient Nondoped and Doped Deep‐Blue OLEDs with CIEy <0.1. Issue 17 (11th March 2021) - Xia, Guoqi; Qu, Cheng; Zhu, Yunlong; Ye, Jianjiang; Ye, Kaiqi; Zhang, Zuolun; Wang, Yue
Abstract: Reported herein is a molecular design strategy of deep‐blue emitters for resolving the lack of highly efficient deep‐blue organic light‐emitting diodes (OLEDs) featuring CIEy (Commission Internationale de l'Eclairage) color coordinates matching the display requirements (<0.1). The strategy is to combine weak spiro‐donor and spiro‐acceptor groups into a linear donor‐π‐acceptor type of thermally‐activated delayed fluorescence molecule through a sterically bulky π‐spacer. The strategy endows an emitter with deep‐blue emission, a narrower emission bandwidth (51 nm in toluene), a high photoluminescence quantum yield (0.95 in toluene), weak concentration quenching, and efficient triplet‐exciton utilization, which are all attractive characteristics for emitters of deep‐blue OLEDs with lower CIEy coordinates. Owing to the rational design, the emitter has realized not only highly efficient doped deep‐blue OLEDs with external quantum efficiencies (EQEs) up to 25.4 % and CIEy less than 0.1 but also so far the most efficient nondoped deep‐blue OLED (EQE up to 22.5 %) with CIE y less than 0.1. Abstract : By combining a weak spiro‐donor and a weak spiro‐acceptor through a sterically bulky π‐spacer, a linear D‐π‐A type of TADF compound is constructed. Highly efficient nondoped (EQEmax : 22.5 %) and doped (EQEmax : 25.4 %) deep‐blue OLEDs with a CIE y of less than 0.1 are realized based on the compound. The nondoped OLED represents the most efficient one achieved so far on the premise of a CIE y of less than 0.1.